Uitkomsgebaseerde onderwys in die lig van moderniteit en postmoderniteit - Froneman, S. (Koers, 2000)
Outcomes-based education in the light of modernity and postmodemityWestern civilization is in the midst of a paradigm shift from the modem era with its technical rationality to the postmodern era with its eclectic and pluralistic perspective. This paradigm shift has far-reaching consequences for education in general and teacher training in particular. Many new ideas in education for example the learner-centred approach, the teacher as facilitator and the emphasis on the interrelatedness of subjects stem from postmodern thinking. If educators are not aware of the differences in thinking between the two paradigms, they will not be able to understand the changes taking place at the moment and could be negatively inclined towards educational reforms. The future debate on the course and direction for education cannot progress if these cultural and philosophical changes are ignored.